Reversal of the metastatic phenotype in Lewis lung carcinoma cells after transfection with syngeneic H-2Kb gene. - Plaksin, D (1988)
High metastatic clones of the murine 3LL carcinoma express greatly reduced levels of H-2Kb major histocompatibility complex class I antigens, while low metastatic clones of the same tumor express high levels of H-2Kb. Induced expression of this antigen after transfection with the H-2Kb gene resulted in conversion of a metastatic to a non- or low-metastatic phenotype. Unlike the parental cells, transfected cells are potent inducers of H-2Kb-restricted syngeneic cytotoxic lymphocytes that kill the Kb-positive clones and cross-react with parental nontransfected cells. Preimmunization of mice with Kb-positive transfectants conferred protection against metastatic spread of malignant cells. Moreover, immunotherapy of metastasis was achieved by immunization with the H-2Kb-transfected cells of animals already carrying a growing local tumor of the parental cells.